Determination of Employee Engagement: Analysis of Servant Leadership, Organizational Commitment, Compensation, and Career Development in Middle-Class College - Yosi Pahala; Lira Agusinta; Nursery Alfarizi Nasution; Esternilus Edwin Lermatan; Reni Dian Octaviani (Dinasti Publisher, 2024)
The study aims to investigate the factors influencing employee engagement in these institutions, with a particular focus on servant leadership, organizational commitment, compensation, and career development. Using a mixed method approach, data will be collected through surveys and interviews from faculty and staff members at a secondary education institution representing the middle class. The method used in this scientific article is quantitative, with the population coming from employees of a campus with various faculties where the distribution of questionnaires is carried out online and in person, dissemination is carried out for one month and returns the results of questionnaires received as many as 37 answers, then this data is processed with the help of SPSS 24. Data analysis with the results of analysis and interpretation is conveyed in the results of this scientific article as a form of answer from the data that has been entered. Organizational Commitment has a significant correlation with employee engagement and employee engagement. This shows the importance of organizational commitment in influencing employee engagement and engagement levels. The correlation between Servant Leadership, Compensation, and Career Development with other variables tends to be weak and not statistically significant. This suggests the need for further research to understand the relationship between these factors and employee engagement and employee engagement. Institutional recommendations can improve employee engagement and their engagement, which in turn can improve overall organizational performance and success.